The Russian registry of primary hyperparathyroidism, latest update - Mokrysheva, Natalia G.; Eremkina, Anna K.; Elfimova, Alina R.; Kovaleva, Elena V.; Miliutina, Anastasiia P.; Bibik, Ekaterina E.; Gorbacheva, Anna M.; Dobreva, Ekaterina A.; Maganeva, Irina S.; Krupinova, Julia A.; Salimkhanov, Rustam H.; Aboishava, Lizaveta A.; et al. (Frontiers in Endocrinology, 2023)
Introduction: Until recently no major epidemiological research of primary hyperparathyroidism (PHPT) has been conducted in the Russian Federation, this led to the creation of the Russian online registry. The objective of this study is to estimate the clinical and biochemical profile, classical and non-classical complications, surgical intervention and medical therapy of the patients with different forms of PHPT in the Russian Federation. Material and methods: The cross-sectional, observational, continuous study was conducted at the Endocrinology Research Centre (Moscow). The present study explored retrospective data from 6003 patients submitted to the Registry between 12.12.2016 and 25.10.2022 from 81 regions of the Russian Federation (http://pgpt.clin-reg.ru/). Results: The median age was 59 [60; 66] years with a female:male ratio of 11.7:1. Symptomatic PHPT was observed in 74.3% while asymptomatic form - only in 25.7% of cases. Bone pathology was the predominant clinical manifestation in 62.5% of cases (n=2293), mostly in combination with visceral complications 45.7% (n=1676). The majority of patients (63.3%) had combined visceral disorders including kidney damage in 51.8% and gastroduodenal erosions/ulcers in 32.3% of patients. Symptomatic patients were older (60 [53; 67] vs 54 [45; 62] years, p<0.001) and had more severe biochemical alterations of calcium-phosphorus metabolism. Cardiovascular disease (СVD) was recorded in 48% of patients, among them the most frequent was arterial hypertension (up to 93.9%). A genetic test was conducted in 183 cases (suspicious for hereditary PHPT) revealing the mutations in MEN1, CDC73, RET genes in 107, 6 and 2 cases, respectively. Surgery was performed in 53.4% of patients with remission achievement in 87%, the relapse/persistence were recorded in 13% of cases. Histological examination revealed carcinoma in 4%, atypical adenoma in 2%, adenoma in 84% and hyperplasia in 11% of cases. Drug therapy was prescribed in 54.0% of cases, most often cholecalciferol. Conclusion: The detection rate of PHPT has increased in the Russian Federation in recent years. This increase is associated with the start of online registration. However, the majority of patients remain symptomatic with significant alterations of phosphorus-calcium metabolism that indicates delayed diagnosis and requires further modifications of medical care.